Dampak Radiasi UV Terhadap Kuat Tarik dan Lifetime Material HDPE Pada Pelampung Aerator - Tarisa Anggraini; Priyambodo Nur Ardi Nugroho; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Aerators play an important role in maintaining shrimp survival in aquaculture ponds. To improve aerator performance, good quality and durability floats are required to support the optimization of aerator loads. Because aerators operate in open areas exposed to sunlight, there is a possibility that aerators will degrade due to exposure to ultraviolet light from the sun. Therefore, this study reviews the impact of ultraviolet light on the decrease in tensile mechanical properties and changes in functional groups in float materials made of HDPE. Tensile test samples were replicated three times in each variation to obtain reliable experimental results, then FTIR testing was performed. The results show that the sample with the highest exposure has the largest decrease in tensile strength, which is about 14%. Based on FTIR analysis, ultraviolet radiation does not reduce functional groups, but reduces the intensity of each functional group. HDPE has an approximate service life of 1664 days.